Upaya Meningkatkan Literasi Dan Numerasi Di Era Digital Pada Siswa Smk Dharma Bhakti Surabaya Melalui Program Kampus Mengajar Angkatan 6 - Reicha Artha Maudia; Diana Juni Mulyati (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
As the times evolve and consumption rates increase, waste management has become one of the primary challenges faced by communities, particularly in the Rw 02 Gunungsari Surabaya area. In an effort to address the negative impacts of production and waste disposal, the city government, especially the Dinas Lingkungan Hidup Surabaya, has initiated the MBKM KZW ( Zero Waste Village ) as an innovative and sustainable solution. Zero Waste is not just a slogan, it is a lifestyle that teaches us to change consumption paradigms and appreciate natural resource. One of the main pillars of the Zero Waste movement is waste reduction. This involves awareness of the sources of waste around us and concrete steps to minimize it. From reducing the use of single-use plastics to choosing products with eco-friendly packaging, every small action has positive impact on the environment. The key to the success of the KZW program is collaboration and active involvement of various stakeholders. This is includes the Dinas Lingkungan Hidup Surabaya, the community of Rw 02 Gunungsari Surabaya, and students from the Universitas 17 Agustus 1945 Surabaya, working together to reduce waste. Innovation in waste management needs to be encouraged. Adopting a Zero Waste lifestyle is not an easy task, but with awareness, education, and sustainable actions, we can collectively create positive change towards a more sustainable and environmentally friendly future. Zero Waste is not just about minimizing waste, it is also about maximizing our potential to live in harmony with nature.